\(x=\cfrac{4ab}{a+b}\) হলে, দেখাই যে, \(\cfrac{x+2a}{x-2a}+\cfrac{x+2b}{x-2b}=2\) [প্রদত্ত \(a\ne0, b\ne 0\) এবং \(a\ne b\)]


\(x=\cfrac{4ab}{a+b}\)
বা, \(\cfrac{x}{2a}=\cfrac{2b}{a+b}\)

[উভয়পক্ষকে 2a দ্বারা ভাগ করে পাই]



সুতরাং, \(\cfrac{x+2a}{x-2a}=\cfrac{2b+a+b}{2b-a-b}=\cfrac{a+3b}{b-a}\)

[যোগভাগ প্রক্রিয়ার সাহায্যে পাই]


আবার, \(x=\cfrac{4ab}{a+b}\)
বা, \(\cfrac{x}{2b}=\cfrac{2a}{a+b}\)

[উভয়পক্ষকে 2b দ্বারা ভাগ করে পাই)]



সুতরাং, \(\cfrac{x+2b}{x-2b}=\cfrac{2a+a+b}{2a-a-b}=\cfrac{3a+b}{a-b}\)

[যোগভাগ প্রক্রিয়ার সাহায্যে পাই]


\(∴\cfrac{x+2a}{x-2a}+\cfrac{x+2b}{x-2b}\)
\(=\cfrac{a+3b}{b-a}+\cfrac{3a+b}{a-b}\)
\(= \cfrac{a+3b}{b-a}-\cfrac{3a+b}{b-a}\)
\(=\cfrac{a+3b-3a-b}{b-a}\)
\(=\cfrac{2b-2a}{b-a}\)
\(=\cfrac{2(b-a)}{(b-a)}=2\) (প্রমাণিত)

Similar Questions